2018
DOI: 10.1016/j.ygyno.2018.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Too many women are dying from cervix cancer: Problems and solutions

Abstract: One woman dies from cervix cancer every 2 minutes, adding up to over 270,000 deaths globally per year. This cancer affects a young population, and hence, the loss of life is staggering. There are many aspects of prevention, screening, and care that are suboptimal. A great deal is known about HPV induced carcinogenesis, yet clinical outcomes have been stagnant over decades. There has been no improvement in cervix cancer survival in the US since the mid-1970s (1). With increased knowledge of the disease and grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 74 publications
1
47
0
2
Order By: Relevance
“…The focus should be directed toward healthcare workers who have concerns about HPV vaccine safety [ 82 ]. It has been reported that more than half a million new cases of cervical cancer are diagnosed annually with high mortality rates registered in poor countries [ 83 , 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…The focus should be directed toward healthcare workers who have concerns about HPV vaccine safety [ 82 ]. It has been reported that more than half a million new cases of cervical cancer are diagnosed annually with high mortality rates registered in poor countries [ 83 , 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14] Screening policies should take into consideration socio-economic factors, which influence disease causation. 15 The introduction of innovative methods for screening of large population should be emphasized. Public awareness on early detection by screening should be encouraged.…”
Section: Discussionmentioning
confidence: 99%
“…Especially in Eastern Africa, cervical cancer was the most frequently diagnosed cancer in women. There were many risk factors that influence cause of cervical cancer, such as high-risk human papillomavirus(hrHPV) infection, smoking, health conditions, economic status and sexual partners (2,3). Compared with 2012 statistics, the incidence of cervical cancer in 2015 had decreased by 1.3% (4), possibly dued to production of HPV vaccine, improvement of living conditions and early screening (5).…”
Section: Introductionmentioning
confidence: 99%